Taxonomic revision of the monotypic genus Psellonus Simon, 1897 (Araneae, Philodromidae) - Malamel, Jobi J.; Nafin, Karunnappilli Shamsudheen; Sankaran, Pradeep M.; Sebastian, Pothalil A. (Zootaxa, 2019)
The monotypic genus Psellonus is revised, including the first description of the male of Psellonus planus Simon, 1897. One new synonymy is proposed: Philodromus kendrabatai Tikader, 1966 = Psellonus planus Simon, 1897 syn. nov.